Analysis of The Use of EXO Brand Ambassador on Scarlett Whitening Instagram Social Media - Nuriyanti, Shinta; Aestetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2024)
Brand Ambassadors in the marketing industry, especially in the digital age where social media plays an increasingly dominant role. The presence of celebrities as brand ambassadors has become a common strategy for brands to strengthen their brand image on social media. EXO's presence as Scarlett whitening brand ambassador on the Instagram platform. The purpose of this research is to analyze the use of EXO brand ambassadors, the focus of this research is on content involving EXO on Scarlett whitening's instagram. this research provides benefits to be able to understand the types of content that are attractive to instagram followers, in order to help in designing more interesting and relevant content. The theory in this research is Brand ambassador theory which will help in developing an understanding of the dynamics of the relationship between celebrities, brands, and consumers in the context of social media. The research method used is qualitative using content analysis. Content analysis will be conducted to identify and evaluate the types of content posted by Scarlett Whitening's Instagram account featuring EXO Brand Ambassador. Primary data will be obtained from Scarlett whitening's Instagram posts related to the presence of EXO as a brand ambassador. Secondary data will be obtained from literature and previous research relevant to this topic. The findings that the use of EXO's Brand Ambassador as a Brand Ambassador succeeded in attracting the attention of Instagram users, increasing interaction, and expanding the reach of Scarlett Whitening products. Scarlett whitening utilizes transference, congruence, credibility, attractiveness and also power. Thus, Scarlett Whitening is effective in achieving promotional goals and providing many positive responses from the products being promoted.